Studi Komparasi Pengetahuan dan Sikap tentang Manajemen Kebersihan Menstruasi Sesudah Pemberian Edukasi Menggunakan Media Audiovisual dengan Booklet Print: Comparative Study of Knowledge and Attitudes regarding Menstrual Hygiene Management After Providing Education Using Audiovisual Media with Printed Booklets - Aniroh, Umi; Tina Mawardika (Universitas Ngudi waluyo, 2024)
Adolescent girls are at risk of health problems, especially in their reproductive health, due to poor menstrual hygiene habits as a result of insufficient knowledge and negative attitudes about menstrual hygiene management. There are many ways to increase knowledge and change attitudes to be more positive, including providing health education through audiovisual media and booklets, but related to the ease of access and interest of young women in obtaining information, it is necessary to evaluate the effectiveness of the two methods which is more efficient in increasing knowledge and promoting positive attitudes regarding menstrual hygiene management in adolescent girls. This study aims to determine the comparison of audiovisual media and booklets on the knowledge and attitudes of adolescent girls regarding menstrual hygiene management at An Nur Ungaran Middle School. This quasi-experimental research uses a two group pretest and posttest design. The sample in this study amounted to 38 respondents consisting of 19 respondents in the audiovisual group and 19 respondents in the booklet group. The sampling technique uses total sampling. The research instrument uses a questionnaire regarding knowledge and attitudes about menstrual hygiene management which has been tested for validity and reliability. The data was analyzed univariately to determine the frequency distribution of the variables and bivariate analysis using the paired to t-test and the independent sample t-test. There is a difference in the average increase in knowledge in the audiovisual and booklet groups, namely 3.002 with a p-value of 0.001 < α (0.05) and there is a difference in the average increase in attitudes in the audiovisual and booklet groups, namely 1.092 with a p-value of 0.001 < α (0 .05) so it can be concluded that there is a significant difference in attitude improvement between the two groups. Interventions using audiovisual media and booklets are able to increase the knowledge and attitudes of adolescent girls regarding menstrual hygiene management, but using audiovisual media is more effective than booklets. It is hoped that audiovisual media will be chosen as a medium in health education in conveying information about menstrual hygiene management to adolescent girls. Abstrak Remaja puteri memiliki risiko terjadi gangguan kesehatan terutama pada kesehatan reproduksinya karena kebiasaan menjaga kebersihan saat menstruasi yang buruk sebagai akibat dari pengetahuan yang kurang dan sikap negatif tentang manajemen kebersihan menstruasi . Banyak cara untuk meningkatkan pengetahuan serta merubah sikap menjadi lebih positif, diantaranya dengan memberikan pendidikan kesehatan melalui media audiovisual dan booklet, namun terkait dengan kemudahan akses serta minat remaja puteri dalam memperoleh informasi, perlu mengevaluasi efektivitas kedua metode mana yang lebih efisien dalam meningkatkan pengetahuan dan mempromosikan sikap positif terkait manajemen kebersihan menstruasi pada remaja putri. Penelitian ini bertujuan untuk mengetahui perbandingan media audiovisual dan booklet terhadap pengetahuan dan sikap remaja putri tentang manajemen kebersihan menstruasi di SMP An Nur Ungaran. Penelitian quasi experiment ini menggunakan rancangan two group pretest and posttest. Sampel dalam penelitian ini berjumlah 38 responden yang terdiri dari 19 responden kelompok audiovisual dan 19 responden kelompok booklet. Teknik pengambilan sampel menggunakan total sampling. Instrumen penelitian menggunakan kuesioner tentang pengetahuan dan sikap manajemen kebersihan menstruasi yang telah diuji validitas dan reliabilitasnya. Data dianalisis secara univariat untuk mengetahui distribusi frekuensi dari variabel dan analisis bivariat menggunakan uji paired sampe t-test dan uji independent sample t-test. menunjukkan ada perbedaan rerata peningkatan pengetahuan pada kelompok audiovisual dan booklet yaitu 3,002 dengan p-value 0,001 < α (0,05) dan ada perbedaan rerata peningkatan sikap pada kelompok audiovisual dan booklet yaitu 1,092 dengan p-value 0,001 < α (0,05) sehingga dapat disimpulkan terdapat perbedaan selisih peningkatan sikap yang bermakna antara kedua kelompok. Intervensi menggunakan media audiovisual maupun booklet mampu meningkatkan pengetahuan dan sikap remaja putri tentang manajemen kebersihan menstruasi, namun lebih efektif menggunakan media audiovisual dibandingkan dengan booklet. Diharapkan media audiovisual lebih dipilih sebagai media dalam pendidikan kesehatan dalam menyampaikan informasi tentang manajemen kebersihan menstruasi pada remaja putri.